Difficult clinical management of antituberculosis DRESS syndrome complicated by MRSA infection: A case report. Issue 11 (March 2017) - Wang, Li; Li, Lin-Feng
Abstract: Rationale: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe drug-induced hypersensitivity reaction characterized by skin rash, fever, blood abnormalities, and multiple organ involvement. The diagnosis of DRESS syndrome is often delayed because of its variable presentation. Prompt withdrawal of the culprit drug is the definitive treatment. DRESS syndrome induced by antituberculosis drugs has rarely been reported. Patient Concerns: A 50-year-old man admitted to our hospital with recurrent episodes of progressive rash, fever, eosinophilia, lymphadenopathy, hepatic, and pulmonary involvement were experienced after repeat trials of the same antituberculosis drugs. Diagnoses: We diagnosed it as DRESS caused by antituberculosis drugs. Interventions: The case responded well to treatment with systemic corticosteroids and intravenous immunoglobulins. However, repeated bouts of infection with methicillin-resistant Staphylococcus aureus occurred during treatment (clavicular osteomyelitis and knee septic arthritis). He was cured after treatment with linezolid. Outcomes: The patient was discharged on day 112. At 8-month follow-up, there was no relapse of drug eruption and joint swelling. Lessons: Early diagnosis and prompt withdrawal of all suspected drugs is a key tenet of the treatment of DRESS. Our case report highlights the risks inherent in delayed diagnosis of DRESS and the challenges in the clinical management of this condition. Pulmonary manifestations with radiological changes on chest X-ray and CT can be seen in DRESS. These changes need to be differentiated from those caused by pulmonary infections. Clavicular osteomyelitis infected with MRSA may be caused by iatrogenic injury during subclavian vein catheterization. This type of MRSA infections should be treated for 4 to 6 weeks. Blood eosinophilia could be a useful marker of disease progression and treatment response in patients with DRESS. However, more experience and clinical evidence is needed to confirm this.